1989
DOI: 10.1159/000226735
|View full text |Cite
|
Sign up to set email alerts
|

Iron, Copper and Zinc Levels in Serum and Cirrhotic Liver of Patients with and without Hepatocellular Carcinoma

Abstract: It has been pointed out that hepatocellular carcinoma (HCC) develops more frequently in cirrhotic liver with siderosis than in liver without iron deposition, that excess copper in hepatocytes inhibits hepatocarcinogenesis, and that an increase in copper and a decrease in zinc are seen in the sera of patients with various malignant tumors. Iron, copper and zinc concentrations in the serum and liver were estimated in normal subjects and cirrhotic patients with and without HCC. Serum copper level was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…This suggests that the serum zinc concentration is determined by the degree and extent of damage of noncancerous regions in the liver, even in patients with HCC. This result supports previous reports that zinc contributes to the occurrence of HCC [26,27]. In addition, it was ascertained that the life expectancy of a patient group with low serum zinc concentrations was worse than that of a group with higher zinc concentrations.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that the serum zinc concentration is determined by the degree and extent of damage of noncancerous regions in the liver, even in patients with HCC. This result supports previous reports that zinc contributes to the occurrence of HCC [26,27]. In addition, it was ascertained that the life expectancy of a patient group with low serum zinc concentrations was worse than that of a group with higher zinc concentrations.…”
Section: Discussionsupporting
confidence: 91%
“…Zn is necessary for proper liver function since it has important antioxidant, anti-inflammatory, and antiapoptotic properties. [196] [191,192] Note. R, rats.…”
Section: Discussionmentioning
confidence: 99%
“…Serum Zn levels were reduced compared with those in healthy controls, while serum Cu levels were increased compared with those in healthy individuals and patients with cirrhosis without HCC. Serum Zn levels were either increased [190,191] or unaffected [192,193] in cirrhotic patients with HCC compared with those in cirrhotic patients without HCC. In HCC patients the serum Cu/Zn ratio was significantly increased and could be used to distinguish cirrhotic from HCC patients [82].…”
Section: Zn and Hepatocellular Carcinomamentioning
confidence: 97%
See 1 more Smart Citation
“…9,10) It has also been reported that in chronic liver diseases, the Cu concentration in the liver parenchyma increases with the progression of disease. 11,12) Tashiro-Itoh et al, in their study on human tissue bearing hepatocellular carcinoma (HCC), reported that the levels of both Cu and MT were increased in well-differentiated cancer but were lower in poorly differentiated cancer, which is in contrast with results from pericancerous hepatic tissue. 13) Ebara et al evaluated the presence and localization of Cu-MT in HCC and non-cancerous hepatic parenchyma in surgically resected specimens from HCC patients using the gel-filtration method, and concluded that accumulation of Cu in small HCC, in which Cu was present as Cu-MT or Cu,Zn-MT, was greater than that in the surrounding liver parenchyma.…”
mentioning
confidence: 99%